Linking Corporate Governance With Investment Growth: Evidence From General Shariah Insurance in Indonesia - Herawati, Mesi (Institut Agama Islam Negeri (IAIN) Curup, 2024)
Purpose: This study aims to examine the role of good corporate governance on investment growth in sharia general insurance companies in Indonesia. This study is motivated by the low return on investment made in sharia general insurance in Indonesia.Design/Method/Approach : This research is a quantitative research with multiple regression analysis method using eviews. The variables in this study consist of one dependent variable and three independent variables. The data used in this study is time series data starting from 2028 to 2019, the sample selection in this study uses a purposive sampling technique consisting of 102 samples.Findings: The results of the study indicate that the board of directors variable (X1) has a significant effect on investment growth, with a calculated t value of 3.533585 greater than the t table of 1.983971519 and a probability value of 0.0006 which is smaller than 0.05. On the other hand, the independent board of commissioners variable (X2) and company size (X3) do not have a significant effect on investment growth. The independent board of commissioners variable has a calculated t value of -0.886408 smaller than the t table and a probability value of 0.3776> 0.05, while the company size variable has a calculated t value of -0.451771 smaller than the t table and a probability value of 0.6524> 0.05.Originality/Values: This research provides a major contribution regarding the importance of implementing good corporate governance and its relationship to investment growth.